SPIRITUAL LEADERSHIP SEBAGAI PENDEKATAN MANAJEMEN SUMBER DAYA MANUSIA DI PENDIDIKAN ISLAM - Lailatul Mukaromah; Siti Aimah (CV. Adiba Aisha Amira, 2026)
This study aims to explore the implementation of spiritual leadership as a human resource management approach to improving teacher performance in Islamic educational institutions.The study used a qualitative case study approach, collecting data through in-depth interviews, participant observation, and documentation with teachers and institutional leaders.This approach emphasizes the integration of spiritual values, such as role models, integrity, and moral responsibility, into human resource management, which are rarely systematically applied in contemporary Islamic education.The results show that spiritual leadership strengthens teachers' commitment, discipline, and the quality of learning, and creates a meaningful work climate. This provides a practical reference for improving the quality and performance of Islamic educational institutions.